Development and Validation of a Novel RP-HPLC Method for Quantification of Maralixibat, Odevixibat, and their related impurities in Pharmaceutical Formulations: Research Article (Journal of Pharma Insights and Research, 2025)
A novel, sensitive, and robust reverse-phase high-performance liquid chromatography (RP-HPLC) method has been developed and validated for the simultaneous quantification of Maralixibat, Odevixibat, and their related impurities in pharmaceutical formulations. The chromatographic separation was achieved using a Waters Alliance-e2695 system equipped with an Inertsil ODS C18 column (250mm × 4.6mm, 5µm) at ambient temperature. The mobile phase consisted of acetonitrile and KH2PO4 buffer (pH 3.0 adjusted with orthophosphoric acid) in a gradient elution mode. The flow rate was maintained at 1 mL/min with detection at 232 nm using a photodiode array detector. The method demonstrated excellent linearity in the range of 118.75-712.50 µg/mL for Maralixibat and 5.0-30.0 µg/mL for Odevixibat, with correlation coefficients greater than 0.999. The developed method exhibited good precision with RSD values less than 2.0% for both system and method precision. Recovery studies at three concentration levels (50%, 100%, and 150%) showed excellent accuracy with mean recoveries ranging from 98.0% to 102.0%. The method successfully separated all impurities from the main compounds with good resolution and peak symmetry. The number of theoretical plates was found to be more than 2000, and the tailing factor was less than 2 for all analytes. This method proves to be suitable for routine quality control analysis and stability studies of Maralixibat and Odevixibat in pharmaceutical formulations